Oral isotretinoin for acne: a complete overview. Issue 8 (3rd August 2022) - Villani, Alessia; Nastro, Francesca; Di Vico, Francesca; Fabbrocini, Gabriella; Annunziata, Maria Carmela; Genco, Lucia
ABSTRACT: Introduction: Acne is one of the most common and widespread skin conditions, affecting the health as much as patients' quality of life. A wide variety of treatments for acne, topical and systemics, could be prescribed, depending on its degree of severity. Isotretinoin, a derivative of retinol, has been widely used for the treatment of severe forms of acne and those forms not responding to conventional treatments. In literature, there are several studies describing its efficacy, also reporting side-effects related to the drug; therefore, this has led the scientific community to request further studies qualifying its characteristics and comparing its efficacy and safety with other classic acne treatments, as well as with different treatment regimes, in order to find the dose with the best efficacy/safety ratio. Areas covered: The aim of this article is to provide a complete overview on the use of oral isotretinoin for the treatment of acne describing the efficacy, safety, and tolerability of the drug. Expert opinion: Oral isotretinoin represents a valid therapeutic alternative in treating severe and mild-to-moderate acne lesions, also reducing scarring damage. There are no standardized protocols regarding the use of oral isotretinoin and its association with other therapies; however, the correct patient selection and a tailored treatment protocol according to acne lesions severity and type should be considered in order to obtain optimal results.